2019
DOI: 10.4103/ua.ua_167_18
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendicovesicostomy and ileovesicostomy: A step-by-step technique description in neurogenic patients

Abstract: Aims:This study aims to describe our surgical technique and report our preliminary experience with laparoscopic ileal or appendicovesicostomy in adult patients with neurogenic bladder caused by spinal cord injury.Subjects and Methods:From January 2014 to March 2017, seven patients were submitted to an appendicovesicostomy under Mitrofanoff procedure and two patients to an ileovesicostomy under Yang-Monti procedure by laparoscopy. Clinical indications were patients with a history of neurogenic bladder secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Recent literature also shows good results with a continence rate at conduit level between 58.40% and 100% [3 ▪ ,5 ▪ ,12 ▪ ,13 ▪▪ ,15 ▪ ,17 ▪▪ ,18 ▪ ].…”
Section: Short- and Long-term Surgical Outcomesmentioning
confidence: 78%
See 3 more Smart Citations
“…Recent literature also shows good results with a continence rate at conduit level between 58.40% and 100% [3 ▪ ,5 ▪ ,12 ▪ ,13 ▪▪ ,15 ▪ ,17 ▪▪ ,18 ▪ ].…”
Section: Short- and Long-term Surgical Outcomesmentioning
confidence: 78%
“…The series of Costa et al reported the lowest rate of stomal stenosis (11%) [3 ▪ ]. This low rate could be explained by the use of a silicon plug and closer follow-up when a stomal stenosis was identified.…”
Section: Short- and Long-term Surgical Outcomesmentioning
confidence: 95%
See 2 more Smart Citations
“…В настоящее время все больше распространяется и развивается лапароскопия, в том числе в реконструктивной урологии у детей, и аппендиковезикостомию по Митрофанову это развитие не обошло стороной. Среди абсолютных преимуществ лапароскопической аппендиковезикостомии -меньшая травматичность операции, отличный косметический результат и сокращение сроков пребывания больного в стационаре [33][34][35]. Данная операция достаточно сложна технически, поэтому выполнять ее должен опытный хирург, обладающий хорошими навыками в области лапароскопии.…”
unclassified